The Use of Ipad in Learning Islamic Religion Education at the Eighth Graders of Sabilurrasyad Junior High School, Bojong Ngampel Kendal - Muzdalifah; Wahyuningsih Sri; Mashuri Muhammad (MATEC Web of Conferences, 2018)
This study aims at finding the use of Ipad in learning Islamic Religion Education at the eighth graders of Sabilurrasyad Junior High school, Bojong Ngampel Kendal.This study used a qualitative research method. Data were gathered through an observation, indepth-interview and documentation. The results of this study indicate that the use of Media of Ipad Learning in Islamic Religion Education Class at the eighth graders of Sabilurrasyad Junior High School, Bojong Ngampel Kendal is considered effective. Furthermore, the average value of Islamic religion education after the implementation of Ipad media is higher that is 85.67 compared to the previous one 81.14. The supporting factors of the Ipad media are the internet network provided by the school, training from the Information Technology Development Agency, Ipad interestingly attracts students’ attention and motivation, iPad can present material in audio visual form. Meanwhile, the inhibiting factors of using ipad are limited battery power or usage, unstable internet network, students’ lack of knowledge in using ipad, and there is no filter to block inappropriate sites.